Non Enhanced Helical Ct Scan In Visualization Of Normal Appendix - Ameen, May Khalid (Journal of the Faculty of Medicine Baghdad, 2006)
Purpose: To evaluate the frequency of visualization, thickness, and anatomical features of the normal appendix at nonenhanced helical computed tomography (CT). Materials and methods : Two radiologists prospectively iterpreted, in consensus, the abdominal CT scans of 140 patients who were examined for renal colic assessment. They were blinded to patients’ surgical history regarding a previous appendectomy. No contrast material was used. The frequency of visualization, and the two – wall thickness of normal appendix were recorded, as well as the anatomical features of the appendix and the effect of adequasy of intraperitoneal fat on identification of the appendix. Results : The prevalence of appendectomy was 9% (13 of 140 patients). The sensitivity, specificity, positive and negative predictive values, and accurasy of visualization of normal appendix were 77%, 85%, 98%, 27%, and 77% respectively. The frequency of visualization was lower in patients with less nintraperitoneal fat. The mean thickness of normal appendix if no intraluminal content was visualized was 6.6 mm+ 1.0 mm, and the mean thickness excluding visualized intraluminal content was 3.6mm + 0.8 mm. Conclusion : Most normal appendices are seen at nonenhanced helical CT. The thickness of normal appendix, when the content is not recognizable, overlaps the values currently used to diagnose appendicitis at CT.